Classification of life satisfaction by occupational gaps and its characteristics among older adults with care needs - Yuka Misu; Shintaro Hayashi; Taisei Yamamoto (SAGE Publishing, 2024)
Objective Occupational therapy aims at enhancing people's life satisfaction, it is important to focus on the occupational gap between "what they want to do" and "what they actually do." This study aimed to describe the characteristics of occupational gap of older adults with care needs who are residing at home, and clarify how the occupational gap patterns classify their life satisfaction. Method The Occupational Gap Questionnaire was used to assess the occupational gaps of 209 older adults with care needs (80.1 ± 7.5 years old, 42.1% male), and a Classification and Regression Tree analysis was performed. Results The most important factor in classifying participants' life satisfaction was the number of social activities that "they do and want to do," followed by the number of instrumental activities of daily living (IADLs) that "they do not do but want to do". Conclusion Our results suggest that promoting participation in social activities and IADLs that participants want to do may improve life satisfaction even when care is needed. Our findings indicate that it is important not only to reduce the occupational gap but also to increase the number of meaningful activities they want to do.